Enhancing Automotive Engineering Education with Interactive Virtual Simulation: A Research Perspective - Qiyu Wang (Computer fraud & security, 2025)
With the continuous progression of computer software and hardware technologies, particularly 3D engine technology, interactive virtual simulation technology has achieved an increasingly realistic emulation of the physical characteristics of the real world. It has consequently found extensive applications across diverse fields, including gaming, military, and industrial sectors. China, being a significant global force in automobile research, development, production, and manufacturing, has consistently exhibited a robust demand for automotive industry professionals. In an endeavor to cultivate applied undergraduate talents commensurate with the requirements of China's automotive sector, we have initiated the introduction of virtual simulation technology into automotive engineering education and established a virtual simulation experimental teaching center. This center is structured into three integral components: a teaching hub, a research and innovation nexus, and an experiential facility. Specifically, it encompasses a new energy vehicle virtual simulation platform, a VR walking platform, and a creative development platform. These platforms are empowered to conduct a variety of experimental undertakings, such as intelligent connected vehicle algorithm virtual simulation testing experiments, vehicle power performance testing experiments, new energy electric vehicle structure and principle training simulations, and new energy vehicle powertrain assembly simulation training. Following over two years of pedagogical implementation, the virtual simulation experimental teaching center has garnered unanimous acclaim from both faculty and students. It has effectively buttressed the college's educators and learners in executing teaching reforms and engaging in subject competition activities related to new energy vehicles, thereby making a substantial contribution to the development of automotive education.